Penerapan Prinsip Komunikasi Islam Qaulan Baligha Ustadz Abdul Somad di Media Sosial Youtube - Afdal; Ansar Akil; Said, Nurhidayat (Danudirja Setyabudi Nusantara, 2025)
This study examines the implementation of Islamic communication principles in Ustadz Abdul Somad's (UAS) da'wah content on YouTube. The research specifically analyzes how UAS applies three fundamental Islamic communication concepts: qaulan baligha (eloquent speech), qaulan sadida (truthful speech), and qaulan ma'rufa (kind speech) in delivering religious messages encompassing matters of faith (akidah), Islamic law (syar'i), and moral values (akhlak). Through qualitative library research methodology, this study systematically analyzes data from academic literature, scholarly articles, and validated sources focusing on UAS's da'wah content and Islamic communication principles. The findings reveal that UAS effectively implements these principles through clear, precise, and wisdom-filled messages on YouTube, demonstrating exceptional rhetorical skills that resonate with diverse audiences across Indonesia. This research contributes to understanding the effectiveness of Islamic communication principles in digital da'wah and highlights UAS's significant role in shaping contemporary religious discourse through social media platforms in Indonesian society.